Acceptance of Assistive Machine Feet Technology for Psychological Well Being among Disability Family : Single Subject Research - Ridwan, Moch; Tarsidi, Iding (Journal of Education for Sustainability and Diversity, 2023)
The aims of this study is analysis the acceptance of assistive machine feet technology for psychological well-being among families with disabled members. The research method used is a single-subject design, which involves collecting data from individual participants over time. The study examines how the use of assistive machine feet technology affects the psychological well-being of family members with disabilities and their overall acceptance of the technology. The results of the study could provide valuable insights into the potential benefits of assistive machine feet technology for individuals with disabilities and their families.